THE SYMPTOM AND MEDICATION MONITORING WITH LUPIE DIARY IN PEDIATRIC SYSTEMIC LUPUS ERYTHEMATOSUS - Arie Kusumaningrum; Nadia Zahra Amelia (Department of Nursing, Faculty of Medicine, Universitas Sriwijaya, 2026)
Pediatric systemic lupus erythematosus (pSLE) in low-and-middle-income countries often leads to rapid organ damage due to complex treatment regimens and limited specialized care. Effective home-based symptom monitoring is critical to detect early flares, yet conventional tracking is often suboptimal, necessitating tailored digital health solutions like the